Five pillars of Islam in relation with physical and spiritual health - Zaw, Cho Cho; ., Myat Min @ Mohd Omar (2016)
This study aimed to examine five pillars of Islam and their relationship with physical and spiritual health. The five pillars of Islam are the foundation of Muslim life, considered mandatory by believers, and Muslims are required to observe them with utmost devotion. They are summarized as Shahadah, Salah, Zakat, Sawn, and Hajj. The first pillar of Islam, declaration of faith (Shahadah) includes complete submission to the will of Allah (SWT) by believing in Him. Spirituality in general is defined as “religious belief or the spiritual quality of something”, “a search for the sacred”, “personal growth, or an encounter with one's own inner dimension”. The World Health Organization (WHO) mentions spiritual health as one of four dimensions to well-being; physical, mental, social, and spiritual”. Moreover, holistic nursing practice includes treating people as a whole, attending to client’s physiological, psychological, and spiritual needs. Thus, this study intends to further explore the unitary aspect of Islam that permeates each of the pillars, and their effects on physical and spiritual well-being. Five pillars of Islam are discussed from the Quran, Alhadith, and Sunnah (the sayings and traditions of the Prophet) as baselines, and further added the knowledge of the Islamic scholars. And it is noted that our practices based on the five pillars of Islam have not only positive effects on physical but also spiritual health. This paper pointed out that while performing obligatory duties as stipulated by Islam, one can achieve spiritual enhancement as well as physical strength and well-being.